Water level effects on breaking wave setup for Pacific Island fringing reefs. Issue 2 (12th February 2014) - Becker, J. M.; Merrifield, M. A.; Ford, M.
Abstract The effects of water level variations on breaking wave setup over fringing reefs are assessed using field measurements obtained at three study sites in the Republic of the Marshall Islands and the Mariana Islands in the western tropical Pacific Ocean. At each site, reef flat setup varies over the tidal range with weaker setup at high tide and stronger setup at low tide for a given incident wave height. The observed water level dependence is interpreted in the context of radiation stress gradients specified by an idealized point break model generalized for nonnormally incident waves. The tidally varying setup is due in part to depth‐limited wave heights on the reef flat, as anticipated from previous reef studies, but also to tidally dependent breaking on the reef face. The tidal dependence of the breaking is interpreted in the context of the point break model in terms of a tidally varying wave height to water depth ratio at breaking. Implications for predictions of wave‐driven setup at reef‐fringed island shorelines are discussed.